FENOMENA OPTIMALISASI PLATFORM E-PESANTREN UNTUK MENINGKATKAN HAFALAN AL-QUR'AN DI MADRASAH IBTIDAIYAH AL-BAQIYATUSH SHALIHAT DAN MADRASAH IBTIDAIYAH AN-NURUL BURHANI - Husnaini; Fitriyani Kosasih; Eliva Sukma Cipta (STKIP Subang, 2026)
This study aims to analyze the phenomenon of optimizing the E-Pesantren platform to improve students' Qur'an memorization at Madrasah Ibtidaiyah Al-Baqiyatush Shalihat and Madrasah Ibtidaiyah An-Nurul Burhani. The study employed a qualitative approach with a multi-site research design to obtain a comprehensive understanding of the implementation of the digital platform in both Islamic elementary schools. Research participants consisted of principals, Tahfiz teachers, E-Pesantren administrators, parents, and students, who were selected using purposive sampling. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings indicate that the E-Pesantren platform has significantly supported the management of the Tahfiz program by facilitating the recording of memorization targets, monitoring daily recitation, documenting students' memorization progress, and strengthening communication between teachers and parents. The platform also enhanced students' learning motivation through systematic evaluation and continuous monitoring of memorization achievements. However, several challenges were identified, including differences in teachers' digital literacy, limited internet connectivity, and varying levels of parental participation. The study concludes that optimizing the E-Pesantren platform contributes positively to improving Qur'an memorization management when supported by competent human resources, adequate technological infrastructure, institutional commitment, and strong collaboration among schools, teachers, students, and parents. Integrating digital technology with traditional Tahfiz learning methods creates a more effective, structured, and sustainable learning system while preserving the essential values of Islamic education.